A scoping review on the impact of austerity on healthcare access in the European Union: rethinking austerity for the most vulnerable - Julia Nadine Doetsch; Clara Schlösser; Henrique Barros; David Shaw; Thomas Krafft; Eva Pilot (BMC, 2023)
Abstract Background There is consensus that the 2008 financial and economic crisis and related austerity measures adversely impacted access to healthcare. In light of the growing debt caused by the COVID-19 crisis, it is uncertain whether a period of austerity will return. Objective This study aims to provide a structured overview of the impact of austerity policies in the EU-28 zone, applied in response to the Great Recession, on access to health care for the adult population, using the five access dimensions by Levesque et al. (2013). Methods This study followed the PRISMA extension for Scoping Reviews guideline. Medline (PubMed) and Web of Science were searched between February 2021 and June 2021. Primary studies in the English language published after the 1st of January 2008 reporting on the possible change in access to the healthcare system for the adult population induced by austerity in an EU28 country were included. Results The final search strategy resulted in 525 articles, of which 75 studies were reviewed for full-text analysis, and a total of 21 studies were included. Results revealed that austerity policy has been primarily associated with a reduction in access to healthcare, described through four main categories: i) Increase in rates of reported unmet needs (86%); ii) Affordability (38%); iii) Appropriateness (38%); iv) and Availability and Accommodation (19%). Vulnerable populations were more affected by austerity measures than the general population when specific safeguards were not in place. The main affected adult vulnerable population groups were: patients with chronic diseases, elderly people, (undocumented) migrants, unemployed, economically inactive people and individuals with lower levels of education or socioeconomic status. Conclusion Austerity measures have led to a deterioration in access to healthcare in the vast majority of the countries studied in the EU-28 zone. Findings should prompt policymakers to rethink the fiscal agenda across all policies in times of economic crisis and focus on the needs of the most vulnerable populations from the health perspective.